Lembaga Pendidikan Islam Terpadu - Mualimin, Mualimin (Universitas Islam Negeri Raden Intan Lampung, 2017)
Education in Indonesia only recognizes three models of educational institutions namely Islamic boarding schools, madrasas, and schools (general). The purpose of this article is to explain the phenomenon of the birth and development of the Integrated Islamic School in Indonesia, the philosophy and ideology of the education of the Integrated Islamic School that distinguishes from existing educational institutions, to the impact caused by the development of these schools. The results of this study can explain why the development of the Integrated Islamic School was so rapid and the response of the community was enthusiastic. The Integrated Islamic School in its application is a school that implements an implementation approach by integrating general education and religious education into a curriculum. The Integrated Islamic School also emphasizes integration in learning methods so that it can optimize the cognitive, affective, and conative domains. The Integrated Islamic School also combines aqliyah, ruhiyah, and jasadiyah education. In its implementation, it combines the involvement and active participation of the learning environment, namely school, home and community.